1976
DOI: 10.1159/000169771
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ischemia and Infarction on Regional Content of Adenine Nucleotides and Derivatives in Canine Left Ventricle<sup>1</sup>

Abstract: Samples of myocardium from four areas of ischemic and infarcted canine ventricle were examined over a 20-day period for content of the three adenine nucleotides as well as inosine, hypoxanthine, adenosine, and inosine monophosphate. The adenosine triphosphate (ATP) content of central and peripheral areas within the infarct fell to 11% and 8% of control, respectively, 1 day after coronary occlusion. The total adenine nucleotide (TAN) content in these areas fell to 17% of control and showed no significant recove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1979
1979
1999
1999

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 21 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…Consequently, there is a transient but substantial increase in myocardial content of nucleotide derivatives (14,15,25). Studies have demonstrated important effects o f these derivatives on the myocardium and coronary vasculature (28,30).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, there is a transient but substantial increase in myocardial content of nucleotide derivatives (14,15,25). Studies have demonstrated important effects o f these derivatives on the myocardium and coronary vasculature (28,30).…”
Section: Introductionmentioning
confidence: 99%